2016
DOI: 10.1371/journal.pone.0161507
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Receptor-Expressing Regulatory T Cells Are Highly Activated, Th2 Biased and Suppress CD4 T Cell Proliferation through IL-10 and TGFβ Release

Abstract: Immunomodulatory Foxp3+ regulatory T cells (Tregs) form a heterogeneous population consisting of subsets with different activation states, migratory properties and suppressive functions. Recently, expression of the IL-33 receptor ST2 was shown on Tregs in inflammatory settings. Here we report that ST2 expression identifies highly activated Tregs in mice even under homeostatic conditions. ST2+ Tregs preferentially accumulate at non-lymphoid sites, likely mediated by their high expression of several chemokine re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 62 publications
(87 reference statements)
8
96
2
Order By: Relevance
“…Expression of the IL-33 receptor, ST2, has been associated with potent Treg function in murine models. [24][25][26] Indeed, we found ST2 to be particularly enriched in CNS Treg in EAE (Figure 4a). IL-33 is highly expressed in the CNS in both EAE and MS ( Figure 4b).…”
Section: Resultsmentioning
confidence: 76%
“…Expression of the IL-33 receptor, ST2, has been associated with potent Treg function in murine models. [24][25][26] Indeed, we found ST2 to be particularly enriched in CNS Treg in EAE (Figure 4a). IL-33 is highly expressed in the CNS in both EAE and MS ( Figure 4b).…”
Section: Resultsmentioning
confidence: 76%
“…ST2 was first shown to be selectively expressed by Th2 cells . Later studies found ST2 expression on other cell types, including macrophages, dendritic cells, basophils, mast cells, regulatory T cells, and ILC2s . IL‐33 can drive eosinophil differentiation from bone marrow precursors in vitro and stimulate cytokine production in eosinophils and mast cells .…”
Section: Epithelial Cell‐derived Cytokines and The Atopic Marchmentioning
confidence: 99%
“…However, alternatively, T reg ‐derived Amphiregulin may also contribute to the survival and expansion of tissue‐resident T regs upon injury. Because it was also further shown that T1/ST2‐expressing T reg populations preferentially express high levels of integrin‐ α V and low levels of IL‐10, it is tempting to speculate that this constitutive expression of Amphiregulin by tissue‐resident T regs may also lead to a constitutive, low‐level release of bio‐active TGF β , which may contribute to ongoing regeneration of tissues and to a low‐level immune‐suppressive environment in the surrounding of Amphiregulin‐expressing tissue‐resident T reg populations, which might be an evolutionary advantage for instance in inflammation‐prone tissues, such as fatty tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Amphiregulin‐expressing T regs are typically restricted to tissue‐resident T reg populations and thus suggest an organ‐specific role for T reg ‐expressed Amphiregulin . These tissue‐resident T reg populations also preferentially express the IL‐33 receptor, T1/ST2 . The role of T1/ST2 expression on T regs currently remains unresolved.…”
Section: The Function Of Regulatory T‐cell‐derived Amphiregulinmentioning
confidence: 99%